Workforce practices of orthodontists in Australia: now and in the future - Wang Andrew; Meade Maurice J. (Australasian Orthodontic Journal, 2025)
To investigate current and future workforce practices of qualified orthodontists (QOs) and trainee orthodontists (TOs) in Australia.